New records of invasive tubeworms (Ficopomatus, Serpulidae) in Mexico - Tovar Hernández, María Ana; De León González, Jesús Ángel; Kupriyanova, Elena K. (Cambridge University Press, 2022)
Ficopomatus Southern, 1921 is a serpulid genus currently composed of six species, two of which (F. enigmaticus and F. miamiensis) are reef-builders. The former has invaded subtropical and warm-temperate estuaries worldwide, causing environmental and economic harm. In this study, Ficopomatus miamiensis and F. uschakovi are reported from brackish-water coastal localities in both Atlantic and Pacific sides of Mexico, including a Biosphere Reserve, estuaries, as well as shrimp and oyster farms. Ficopomatus miamiensis is reported from Veracruz (southern Gulf of Mexico, Mexico territory) and Sinaloa (southern Gulf of California). Ficopomatus uschakovi is reported for the first time in the southern Gulf of Mexico (Mexico territory) and repeatedly recorded in Chiapas (southern Mexican Pacific). There are no phenotypic differences between specimens of F. miamiensis from both coasts of Mexico. Comparison of mitochondrial cytochrome b (Cytb) DNA sequences further support the notion that F. miamiensis from the type locality (Florida) and Atlantic coasts of Mexico is also found along the Pacific coast of Mexico. Morphological variability within specimens of F. uschakovi from a single locality (either Laguna del Ostión or La Encrucijada) in Mexico suggest potential presence of multiple cryptic species. Molecular genetics studies are needed to confirm the taxonomic and invasive status of F. uschakovi.